Highly charged 180 degree head-to-head domain walls in lead titanate - Kalani Moore; Michele Conroy; Eoghan N. O’Connell; Charlotte Cochard; Jennifer Mackel; Alan Harvey; Thomas E. Hooper; Andrew J. Bell; J. Marty Gregg; Ursel Bangert (Communications Physics, 2020)
Domain walls are the basic building blocks of a ferroic system and determine the overall ferroic properties. Here, the authors use aberration corrected scanning transmission electron microscopy to observe the formation of charged needle point domain walls in ferroelectric PbTiO3 and how their characteristics depend on the lead vacancy concentration.